Innovative structural engineering of sustainable and environment‐friendly Cu2ZnSnS4 solar cell for over 20% conversion efficiency. (14th June 2022) - Prabhu, Sudheendra; Pandey, Sushil Kumar; Chakrabarti, Subhananda
Summary: Kesterite Cu2 ZnSnS4 (CZTS) thin‐film technology has been comprehensively investigated over the last decade as a promising candidate in the field of photovoltaic technologies. However, despite numerous strategies to improve the performance, the efficiencies remain stagnant at around 11%. Poorly optimized absorber/buffer interface, non‐absorption of higher wavelength photons, and non‐ohmic back contact are the primary reasons for the poor performance of the CZTS solar cell. The authors of this paper propose a cadmium‐free buffer layer, multiple quantum wells (MQWs) structure, and a back surface field (BSF) layer to overcome these issues, respectively. In this study, the buffer layer, zinc oxysulfide (Zn[O1−x Sx ]) is considered as an alternative to toxic Cadmium Sulfide (CdS) for better band alignment with the CZTS absorber layer. Cu2 ZnSn(Sx Se1−x )4 (CZTSSe) is used as a quantum well material in MQWs to increase photon absorption in CZTS solar cells. Tin selenide (SnSe) is used as the BSF layer to reduce the effect of non‐ohmic back contact and to improve the open‐circuit voltage ( V oc ) of MQW incorporated CZTS solar cells. Detailed analysis and optimization of the modified structure with higher performance are presented. The simulation results obtained provide imperative guidelines for the fabrication of high‐efficiency CZTS solar cells using non‐toxic and earth‐abundant materials.